2013
DOI: 10.1021/jz401603f
|View full text |Cite
|
Sign up to set email alerts
|

Reproducing Deep Tunneling Splittings, Resonances, and Quantum Frequencies in Vibrational Spectra From a Handful of Direct Ab Initio Semiclassical Trajectories

Abstract: A time-dependent semiclassical approach for vibrational spectra calculations is shown to describe deep tunneling splittings, resonances and quantum frequencies in multidimensional multi-well systems, by propagating a very limited number of classical trajectories. The approach is tested on ammonia by evolving eight trajectories on a full-dimensional PES. Quantum effects are reproduced and results are in good agreement with time-independent quantum calculations. All the features are maintained when ab-initio "on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 33 publications
0
82
0
Order By: Relevance
“…[76,77,92,93] To further reduce the computational effort, the multiple coherent time averaged SCIVR (MC SCIVR) has been introduced. [58][59][60][61][62]94] In this Section we provide a more detailed explanation of the "divide-and-conquer" strategy previously introduced elsewhere. [75] The idea is to calculate the power spectrum I (E) of Eq.…”
Section: A Divide and Conquer Strategy For Semiclassical Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[76,77,92,93] To further reduce the computational effort, the multiple coherent time averaged SCIVR (MC SCIVR) has been introduced. [58][59][60][61][62]94] In this Section we provide a more detailed explanation of the "divide-and-conquer" strategy previously introduced elsewhere. [75] The idea is to calculate the power spectrum I (E) of Eq.…”
Section: A Divide and Conquer Strategy For Semiclassical Dynamicsmentioning
confidence: 99%
“…It allows to perform on-the-fly semiclassical molecular dynamics simulations given a few input trajectories. [58][59][60][61][62][63][64][65] The approach is amenable to ab initio direct molecular dynamics, thus avoiding the effort to construct an accurate analytical potential energy surface which may be quite demanding especially for large systems, [66][67][68][69][70][71][72][73][74] and permits to faithfully reproduce quantum effects like quantum resonances, [60] intra-molecular and long-range dipole splittings, and the quantum resonant ammonia umbrella inversion. [62] Nevertheless, all SCIVR methods run out of steam when straightforwardly applied to problems involving large-sized systems.…”
Section: Introductionmentioning
confidence: 99%
“…57,58,62,65,66 Furthermore, they can be associated with ab initio direct dynamics with excellent results, 60,61,6770 a key feature when dealing with molecules the size of glycine or larger. In fact, even if a large variety of very precise PES fitting techniques is available (see, for instance, refs (7183). )…”
Section: Introductionmentioning
confidence: 99%
“…For all these reasons, a semiclassical approach appears to be a straightforward choice for an investigation of “multiwell” effects, as indeed recently demonstrated by two of the authors in studying the ammonia vibrational spectrum. 66 …”
Section: Introductionmentioning
confidence: 99%
“…Several applications [58][59][60][61][62][63][64][65] have demonstrated that this approximation is quite accurate.…”
Section: Semiclassical Initial Value Representation Of the Quantumentioning
confidence: 95%